2013
DOI: 10.13171/mjc.2.4.2013.08.11.23
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study and insecticidal activity of Mentha pulegium L. oils from Morocco against Sitophilus Oryzae

Abstract: Abstract:There is a growing interest of industry to replace synthetic chemicals by natural products with bioactive properties from plant origin. The aim of this study was to validate the therapeutic properties of Mentha pulegium L. by conducting a phytochemical study, to determine the chemical composition of its essential oils (EO) and evaluate its insecticidal activity against stored cereals pests. Leaves and flowers of M. pulegium L.were collected from three regions of the Moroccan Middle Atlas. Phytochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
8
22
1
1
Order By: Relevance
“…Moreover, pulegone can be used in many other fields such as food, cosmetic, and pharmaceutical industries where it is used as a traditional remedy, a flavouring, and a spice. [34,35] These results were in accordance with other studies already carried out in Algeria, India, and Uruguay where M. pulegium EOs were characterized by their high rates of pulegone with percentages of 46.41%, (65.9-83.1%), and 73.4% respectively. [36][37][38] Nevertheless, this composition was different from Mentha pulegium EOs in Morocco and Iran and was characterized by two specific chemotypes: that of piperitone (35.56 and 38%) and piperitenone (21.12 and 33%) where the rate of pulegone did not exceed 2.3 and 6.42%, respectively.…”
Section: Essential Oil Yields and Chemical Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, pulegone can be used in many other fields such as food, cosmetic, and pharmaceutical industries where it is used as a traditional remedy, a flavouring, and a spice. [34,35] These results were in accordance with other studies already carried out in Algeria, India, and Uruguay where M. pulegium EOs were characterized by their high rates of pulegone with percentages of 46.41%, (65.9-83.1%), and 73.4% respectively. [36][37][38] Nevertheless, this composition was different from Mentha pulegium EOs in Morocco and Iran and was characterized by two specific chemotypes: that of piperitone (35.56 and 38%) and piperitenone (21.12 and 33%) where the rate of pulegone did not exceed 2.3 and 6.42%, respectively.…”
Section: Essential Oil Yields and Chemical Compositionsupporting
confidence: 91%
“…[36][37][38] Nevertheless, this composition was different from Mentha pulegium EOs in Morocco and Iran and was characterized by two specific chemotypes: that of piperitone (35.56 and 38%) and piperitenone (21.12 and 33%) where the rate of pulegone did not exceed 2.3 and 6.42%, respectively. [35] Other compounds were poorly represented such as neoisomenthol (4.03%) and p-menth-3-ene (1.29%) ( Table 1). The contribution of monoterpene hydrocarbons in pennyroyal EO did not exceed 2.08%.…”
Section: Essential Oil Yields and Chemical Compositionmentioning
confidence: 99%
“…littoralis , M . persicae among other insect species, toxicity, insect growth inhibition and related effects . Pulegone epoxide, carvone, carvone epoxide, piperitenone oxide, and piperitone have been reported as a strong antifeedants, toxic, and repellent against chewing and sucking insects …”
Section: Resultsmentioning
confidence: 99%
“…Some constituents were found in hydrosol but absent in EO such as suaveolens EO was also piperitenone oxide but with a higher rate than hydrosol (74.69 %) followed by pulegone (2.34 %). Other compounds occurred in EO, but they were absent in hydrosol as limonene (1.85 %), b-pinene (0.65 %), cis-sabinene hydrate (0.53 %), and a-pinene (0.36 %) [27]. The M. suaveolens Ehrh.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Moreover, the M. suaveolens Ehrh. And M. pulegium L.(EOs), extracted from the same plants, have a broad insecticidal effect against S. oryzae adults but the M. suaveolens were also the most effective [26,27]. Similarly, Boughdad et al [38] have reported that the mortality of C. Maculatus adults, induced by M. Suaveolens (piperitenone 34 %) and pennyroyal (pulegone 65 %) EOs, reached 100 % after 3 and 6 days of exposition, respectively.…”
Section: Insecticidal Activity Of Studied Mint Hydrosols Against Blacmentioning
confidence: 99%